Role of grain size on the corrosion resistance of pipeline steels in acidic environment - Meekness Nnoka; Tonye Alaso Jack; Sandeep Yadav; Jerzy Szpunar (Journal of Materials Science: Materials in Engineering, 2025)
Abstract The microstructure of pipeline steels plays an important role in determining their resistance to corrosion. Among various microstructural features, grain size has been a topic of ongoing debate regarding its influence on the corrosion resistance of pipeline steels. While it is established that grain size inversely correlates with yield strength, its impact on corrosion resistance in acidic environments remains unclear. This study investigated the effects of grain size on the corrosion resistance of pipeline steels exposed to an acidic environment. Heat treatments were conducted to vary the grain size from 8 to 19 µm while minimizing contributions from other microstructural features. The findings revealed that reducing grain size significantly enhanced corrosion resistance by promoting passivation. Grain boundaries were identified as the preferred sites for forming protective oxide layers, compared to grain interiors. Consequently, samples with finer grains, which inherently possess a higher density of grain boundaries, exhibited enhanced passivation, resulting in greater surface coverage by protective oxide layers. In contrast, samples with larger grains primarily formed oxide layers along the grain boundaries, leaving the grain interiors more susceptible to attack by corrosive species. Additionally, a phenomenological model was developed based on the experimental results. This model was validated through independent measurements, confirming that passivation coverage increases with decreasing grain size in acidic environment.